2013
DOI: 10.2166/ws.2013.046
|View full text |Cite
|
Sign up to set email alerts
|

Gravity driven membrane filtration system to improve the water quality in rainwater tanks

Abstract: The characterisation of rainwater in metropolitan Sydney and in rural New South Wales was undertaken. The results showed that factors such as the lack of vehicular traffic, air pollution and urban contamination meant that rural rainwater water quality was better. The rain water collected in both metropolitan and rural areas generally complied with the 2004 Australian Drinking Water Guidelines except for parameters such as the pH in both the metropolitan and rural rainwater tanks and the turbidity, and lead lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…However, Kus et al (2013a) reported a good DOC removal performance in GAC filter and GDM process. The reason was that nearly 71% of the DOC was removed by the GAC filter, and membrane post-treatment only contribute to 7% removal efficiency.…”
Section: Organics Removalmentioning
confidence: 92%
See 1 more Smart Citation
“…However, Kus et al (2013a) reported a good DOC removal performance in GAC filter and GDM process. The reason was that nearly 71% of the DOC was removed by the GAC filter, and membrane post-treatment only contribute to 7% removal efficiency.…”
Section: Organics Removalmentioning
confidence: 92%
“…Results showed a good removal performance of heterotrophic bacteria and coliform, but viruses and adenovirus were not effectively removed by the filtration system. Kus et al reported a hybrid process of combination granular activated carbon (GAC) filter and gravity-driven membrane filtration (GDM) for rainwater treatment in lab and pilot scales, and the system reduced the concentration of organics, turbidity and lead below the standards of Australian Drinking Water Guidelines (Kus et al, 2013a, b). Also, they found that after the initial flux decline, the flux reached stable with the value of 0.47 L/m 2 h consistently over the 60 days of the experiment (Kus et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…As pointed out elsewhere, the GDM process may exhibit excellent performance for bacteria and turbidity removals, but the removal efficiencies of organic matter and ammonia nitrogen were undesirable [36][37][38][39]. For example, Peng and Diamantis have reported that the micro-filtration were capable to remove majority of the suspended solids, colloidal particles and pathogens, but the removal rate of dissolved organic matters by alone micro-filtration process was generally lower than 20% [40,41].While Kus et al observed that a GDM process only contribute to 7% removal efficiency of DOC [42]. Similarly, Wu et al have recorded that a pilot GDM systems were able to remove almost all of the particles (i.e., turbidity), 94% of viable cells, and most of TEP (41-85%) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Emerged as a low energy consumption and chemical free technology, the gravity driven membrane (GDM) filtration process is receiving more attentions and has been introduced to treat rainwater prior to use [12][13][14]. Although the GDM process has demonstrated an excellent performance in removing the bacteria and suspended particles in surface water and wastewater treatment, however, this energy-saving technology still has some disadvantages, such as, the removal of low molecular-weight substances is not ideal [15].…”
Section: Introductionmentioning
confidence: 99%
“…Thomas y Greene (1993), investigando la calidad de las aguas de lluvia en contacto con los diversos materiales de los techos en áreas rurales, urbanas e industriales, concluyeron que los materiales de los techos tienen influencia sobre la calidad del agua de lluvia y que las aguas pluviales contaminadas colectadas de los techos se debe principalmente a la contaminación difusa de la deposición atmosférica y del número de días secos que anteceden a un evento lluvioso. Kus et al (2013) también verificaron que los factores como la intensidad Rev. Ambient.…”
Section: Introduccionunclassified